THE INFLUENCE OF FINANCIAL KNOWLEDGE AND FINANCIAL ATTITUDES ON FINANCIAL MANAGEMENT BEHAVIOR IN STIE YAPAN STIE YAPAN'S MANAGEMENT STUDY PROGRAM, SURABAYA - Maya Wulan Avivah; Fida Oktafiani (Jurnal Ekonomi, 2023)
This research delves into the interplay between financial savvy and mindset, and their impact on financial management practices. The study focuses on students enrolled in the management study program at the Surabaya College of Economics and employs purposive sampling to select participants. The sample size of 39 surveys is determined through the application of the Slovin formula, ensuring a 5% confidence level. Quantitative methodologies, specifically SPSS multiple regression analysis, are employed to analyze the gathered data. The findings of this study reveal that while financial attitudes significantly influence financial management behaviors, financial knowledge does not exhibit a corresponding effect. In essence, individuals' attitudes towards finances play a pivotal role in shaping their financial management practices, whereas the level of financial knowledge alone does not appear to have a direct impact.